Teknik Modeling untuk Mengurangi Perilaku Bullying - Fauziyah, Nailul (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Bullying is not a new thing that we encounter. However, in today's disruptive era, bullying behaviour is increasingly rampant and must get serious attention from various parties. The purpose of this study is to determine how effective the modelling method is in reducing student bullying behaviour at MTs Unggulan Nuris Jember. For this study, a quasi-experimental method was used, and a non-matched pre-test and post-test control group was designed. A total of 30 students who showed high category bullying behaviour were divided into two groups: 15 students in the experimental group and 15 students in the control group. The results showed that the posttest scores of the independent sample T-test were different between the experimental group and the control group. Furthermore, the Paired Sample T-Test was used to test whether the modelling technique succeeded in reducing bullying behaviour at MTs Unggulan Nuris Jember. The results showed that the modelling technique succeeded in reducing students' bullying behaviour. Keywords: Bullying, Modeling Technique